Analisis Hubungan Likuiditas, Hutang, Kebijakan Dividen Sebelumnya, dan Profitabilitas Terhadap Kebijakan Dividen Perusahaan Industri Manufaktur di BEI Periode 2008-2010 - Lis Sintha; Sima Sebayang (JURNAL MITRA MANAJEMEN, 2012)
ABSTRACTThe objective of this research is to predict return of investment in equitysecurities. Investors have primarily objective to increase return from theirinvestment. Investors buy stock from public enterprise and may get dividend orcapital gain as its return.Focus on dividend as its return, this research was conducted to examine theeffect of variable Current Ratio (CURR), debt to equity ratio (DER), and Return onEquity (ROE) toward Dividend Per Share (DPS), in manufacturing companies thatlisted in Indonesia Stock Exchange.The data in this study were taken from the financial statements of companiesmanufacturing in Indonesia Stock Exchanges in the period study was fromDecember 31, 2008 until December 31, 2010. To Obtain financial statements fromeach company, the researcher got in from www.idx.co.id, to see the companiesincluded into the manufacturing industry seen form www.duniainvestasi.com, and tosee company paying the dividends in cash, the researchers see it fromwww.ksie.com. The samples and data are collected using purposive samplingmethod.Hypothesis test of this research using Panel Least Square (PLS). regressionresult shows that three independent variables used may affect dependent variablesas much as 94,7% and the rest which is 5,3% explained by other variables that notbeing used in this research model. Result of simultaneous test shows that threeindependent variables together can explain amount of DPS.Conclusion of this research is the results of this research with significant level5% also indicate that ROE has significantly affect on the DPS. While, two otherindependent variables doesn’t have significantly impact to DPS, they are CURR andDER.Keyword: Dividend Per Share, Current Ratio, Debt to Equity Ratio, Return OnEquity, and Panel Least Square.